Chemical Constituen from an Endophytic Fungus Aspergillus sp (SbD5) Isolated from Sambiloto (Andrographis paniculata Nees) - ELFITA ELFITA; MUNAWAR MUNAWAR; MUHARNI MUHARNI; IHSAN IVANTRI (Indonesian Society for microbiology, 2015)
Medicinal plants and their endophytes are important resources for discovery of natural products. Endophytic fungi isolated from medicinal plants more likely exibit pharmaceutical potentials. In the present study, an endophytic fungus Aspergillus sp (SbD5) was isolated from leaves of sambiloto (Andrographis paniculata). The fungus isolate was cultivated in Potato Dextrose Broth (PDB) medium for 7 weeks in static, then extracted with ethyl acetate followed by Thin Layer Chromatography (TLC) test. The results displayed three major spots. Ethyl acetate extract was further separated by column chromatography and recrystallization to obtain three pure compounds. Their structures were determined on the basic of spectroscopic analysis. The compounds is one new benzochromen derivative, 1-(3,8-dihydroxy-4,6,6-trimethyl-6H- benzochromen-2-yloxy)propan-2-one (1), together with two known compounds 5-hydroxy-4-(hydroxymethyl)-2H-pyran-2-one (2) and (5-hydroxy-2-oxo-2H-pyran-4-yl)methyl acetate (3). The antibacterial activities of the compounds were tested using the disk diffusion method against Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Shigella dysenteriae and Salmonella typhi. Â Compound 1 has the highest antibacterial activity followed by compound 2 and 3.